Perbaikan Faktor Daya Pada Beban Listrik Skala Rumah Tangga Dengan Metode Fuzzy Logic - Fachrudin Hunaini; Andhika Ridho Adisyahrudin; Sabar Setiawidayat (JASEE Journal of Application and Science on Electrical Engineering, 2023)
The use of electrical energy is very important for household needs. The greater the use of electrical loads, the greater the need for electrical energy. Every electrical load has a power factor. A low power factor value <0.8 causes power and current usage to be less than optimal. This can be caused by the large use of inductive loads such as electric pumps, electric heaters, TL lamps, and so on. To overcome this, it is necessary to improve the power factor by using capacitors. In this paper, power factor improvement is designed using the Fuzzy Logic method as a data processor embedded in the microcontroller to determine the capacitor variable supported by a sensor to read the values of current, voltage, power, cosphi, and frequency in the electric current as input to the microcontroller and a combination of relays as output to determine the best capacitor value so that the power factor is improved to > 0.8.The use of electrical energy is very important for household needs. The greater the use of electrical loads, the greater the need for electrical energy. Every electrical load has a power factor. A low power factor value <0.8 causes power and current usage to be less than optimal. This can be caused by the large use of inductive loads such as electric pumps, electric heaters, TL lamps, and so on. To overcome this, it is necessary to improve the power factor by using capacitors. In this paper, power factor improvement is designed using the Fuzzy Logic method as a data processor embedded in the microcontroller to determine the capacitor variable supported by a sensor to read the values of current, voltage, power, cosphi, and frequency in the electric current as input to the microcontroller and a combination of relays as output to determine the best capacitor value so that the power factor is improved to > 0.8.